COVID‐19 with and without anosmia or dysgeusia: A case‐control study. Issue 4 (22nd January 2021) - Dev, Nishanth; Sankar, Jhuma; Gupta, Nitesh; Meena, Ramesh Chand; Singh, Charanjit; Gupta, D. K.; Sen, M. K.
Abstract: Various new clinical signs and symptoms, such as dysfunction of smell (anosmia) and taste (dysgeusia) have emerged ever since the coronavirus disease 2019 (COVID‐19) pandemic begun. The objective of this study was to identify the clinical presentation and factors associated with 'new loss/change of smell (anosmia) or taste (dysgeusia)' at admission in patients positive by real time polymerase chain reaction for SARS‐CoV‐2 infection. All adult COVID‐19 patients with new onset anosmia or dysgeusia at admission were included in study group. Equal number of age and gender matched COVID‐19 patients without anosmia or dysgeusia at admission were included in the control group. A total of 261 COVID‐19 patients were admitted during the study period of which 55 (21%) had anosmia and or dysgeusia. The mean ( SD ) age was 36 (13) years and majority were males (58%, n  = 32). Comorbidity was present in 38% of cases ( n  = 21). Anosmia and dysgeusia were noted in more than 1/5th of the cases. Anosmia (96%, n  = 53) was more common than dysgeusia (75%, n  = 41). Presence of both ansomia and dysgeusia was noted in 71% of patients ( n  = 39). On comparing the cases with the controls, on univariate analysis, fever (higher in cases), rhinitis (lower in cases), thrombocytopenia, elevated creatinine and bilirubin (all higher in cases) were significantly associated with anosmia or dysgeusia. On multivariate analysis, only rhinitis (odds ratio [OR]: 0.28; 95% confidence interval [CI]: 0.09–0.83; p  = .02) thrombocytopenia (OR: 0.99; 95% CI: 0.99–0.99; p  = .01) and elevated creatinine (OR: 7.6; 95% CI: 1.5–37.6; p  = .01) remained significant. In this retrospective study of COVID‐19 patients, we found anosmia and dysgeusia in more than 1/5th of the cases. Absence of rhinitis, low platelet counts and elevated creatinine were associated with anosmia or dysgeusia in these patients. Highlights: Anosmia and dysgeusia are frequent findings in SARS‐CoV2 infections. It was noted in more than 1/5th of those infected. Absence of rhinitis, low platelet and elevated creatinine were associated with these symptoms.